Implementation of Islamic Religious Education Based on Religious Moderation: : Case Study at State Secondary Fishing Business School in Tegal City - Lukman, Saeful (Agrikan Jurnal Agribisnis Perikanan, 2023)
Reality This type of research is descriptive qualitative which describes the form of implementation of Islamic religious education based on religious moderation at SUPM N Tegal. The data analysis techniques used are data reduction, data presentation, data validity and conclusion drawing. The results of this research show that: 1) Islamic religious education based on religious moderation at the State SUPM in Tegal City has been optimally seen from a) the preparation of the syllabus and b) the development of the RPP as in the syllabus itself there is an insertion regarding religious moderation while in the RPP The value of religious moderation used is realized either by learning approaches or models as well as by adapting material that contains the value of religious moderation. 2) The reality of SUPM's religious moderation from religious differences for students in reality does not create barriers and barriers for th/em in carrying out their worship, communication and social interactions. All of them follow the routine activities on the school's agenda, whether they are individually or as a group. In carrying out worship for SUPM students, places of worship such as mosques, churches and temples have been prepared according to their respective religions. 3) The impact of Islamic religious education based on religious moderation can form students who have character and are able to uphold the values of religious moderation. The attitude of religious moderation for SUPM Tegal students includes; tolerant attitude, rejecting acts of violence, and respecting diverse local cultures.